Penyuluhan Dan Pemeriksaan Kesehatan Gratis Dalam Upaya Deteksi Dini Hipertensi Pada Masyarakat - Abdul Rivai Saleh Dunggio; Tata Mahyuvi; Hendra Dwi Kurniawan; Fara Khansa Azizah; Sara Surya; Azmi Wijayanti (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Hypertension is a non-communicable disease (NCD) whose prevalence continues to increase in Indonesia and is a major risk factor for heart disease, stroke, and kidney failure. Lack of public knowledge about hypertension and low awareness of the need for regular health check-ups often results in hypertension going undetected early. This community service activity aims to increase public knowledge and awareness about hypertension through health education and free blood pressure checks. The activity was conducted in the neighborhood unit (RW) 05, X Village, and involved 102 participants aged 25–70 years. The activities included interactive health education, blood pressure checks, short interviews, and healthy lifestyle education. The results showed an increase in public knowledge, and 28 participants (27.4%) had blood pressure above normal, most of whom had never had a routine check-up before. Participants expressed satisfaction and found this activity very helpful and hoped that similar activities would be conducted regularly. This activity demonstrates that free health education and check-ups are very beneficial in increasing public awareness of hypertension and have the potential to prevent complications through early detection.